COMPOSITION OF LIPIDS AND FATTY ACIDS IN MUSCLE TISSUE OF CHUB MACKEREL SCOMBER JAPONICUS - L. V. Shulgina; T. A. Davletshina; A. M. Pavlovsky; E. A. Solodova; K. G. Pavel (Известия ТИНРО)
Composition of fatty acids of lipids in muscle tissue of chub mackerel is determined, in dependence on its body size. For the small-sized mackerel (< 20 cm), the lipids content is evaluated as 8.5 ± 0.5 % of the body weight, whereas for the large-sized fish (> 20 cm) it is 23.2 ± 1.2 %. The lipids of mackerel are distinguished by high portion of phospholipids that reaches 14.9 % for the small-sized fish and 8.4 % for the large-sized fish. The portion of unsaturated fatty acids is 74.5 % for the small-sized fish and 77.5 % for the large-sized fish. The portions of monounsaturated and polyunsatuarted fatty acids are 34.5 % and 36.2 % for the small-sized fish and 37.9 % and 36.6 % for the large-sized fish, respectively. The main part of the polyunsaturated fatty acids (85.0–86.2 %) is represented by the fatty acids of family n-3, among which docosahexaenoic (DHA) and eicosapentaenoic (EPA) acids dominate; stiоridovoic fatty acid of this family (18:4 n-3) is presented, as well, that is essential for a human organism functioning. High biological value is determined for the lipids of chub mackerel, taking into account their chemical composition. Daily demands of an adult human body for these valuable unsatuarated fatty acids could be satisfied with 100 g of meat of chub mackerel, irrespectively on its size.